Proceedings of the First ACM Conference on Learning @ Scale Conference 2014
DOI: 10.1145/2556325.2566247
|View full text |Cite
|
Sign up to set email alerts
|

Demographic differences in how students navigate through MOOCs

Abstract: The current generation of Massive Open Online Courses (MOOCs) attract a diverse student audience from all age groups and over 196 countries around the world. Researchers, educators, and the general public have recently become interested in how the learning experience in MOOCs differs from that in traditional courses. A major component of the learning experience is how students navigate through course content.This paper presents an empirical study of how students navigate through MOOCs, and is, to our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(151 citation statements)
references
References 12 publications
9
127
2
13
Order By: Relevance
“…The most active participants, the Social Engagers, were the oldest participants on average and most of them achieved a certificate. These findings are consistent with the literature (Breslow et al, 2013;Guo & Reinecke, 2014;Ho et al, 2014;Huang, Dasgupta, Ghosh, Manning, & Sanders, 2014;Kizilcec et al, 2013;Onah et al, 2014). According to the social-constructivism approach, the social context and relationships with others are crucial to a process of negotiating meaning and developing new skills (Anders, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The most active participants, the Social Engagers, were the oldest participants on average and most of them achieved a certificate. These findings are consistent with the literature (Breslow et al, 2013;Guo & Reinecke, 2014;Ho et al, 2014;Huang, Dasgupta, Ghosh, Manning, & Sanders, 2014;Kizilcec et al, 2013;Onah et al, 2014). According to the social-constructivism approach, the social context and relationships with others are crucial to a process of negotiating meaning and developing new skills (Anders, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This is obvious, for example, when observing the different hours of the day that the students access the online course in our pilot study. But previous work has reported that although most of the participants in a MOOC tend to follow a linear path through the course content, these paths can vary depending on characteristics such as the age or the country of origin [10]. In addition, differences were observed on the activity patterns in each of the courses.…”
Section: Lessons Learnedmentioning
confidence: 95%
“…Research on MOOC video interactions are usually centered on analyzing lecture-to-lecture navigation strategies [5], predicting dropout [6,15] and in-video dropouts [7]. Among these work, only [15,7] contain click-level video analysis.…”
Section: Mooc Analysismentioning
confidence: 99%